Photostability of the deprotonated forms of the UV filters homosalate and octyl salicylate: molecular dissociation versus electron detachment following UV excitation. Issue 28 (6th July 2022) - Wong, Natalie G. K.; Rankine, Conor D.; Anstöter, Cate S.; Dessent, Caroline E. H.
Abstract : Laser photodissociation of deprotonated salicylates reveals that electron detachment outcompetes molecular dissociation following photoexcitation due to the locations of the minimum energy crossing points on the excited state surfaces. Abstract : While common molecular anions show a strong propensity to undergo electron detachment upon UV excitation, this process often occurs in competition with molecular ion dissociation. The factors that affect the balance between these two major possible decay pathways have not been well understood to date. Laser photodissociation spectroscopy of the deprotonated forms of the UV filter molecules, Homosalate (HS) and Octyl Salicylate (OS), i.e. [HS − H] − and [OS − H] −, was used to acquire gas-phase UV absorption spectra for [HS − H] − and [OS − H] − via photodepletion from 3.0–5.8 eV. No photofragmentation ( i.e. dissociation of the ionic molecular framework) was observed for either [HS − H] − and [OS − H] − following photoexcitation, revealing that electron loss entirely dominates the electronic decay pathways for these systems. High-level quantum chemical calculations were used to map out the excited states associated with [HS − H] − and [OS − H] −, revealing that the minimum-energy crossing points (MECPs) between the S1 and S0 states are located in elevated regions of the potential energy surface, making internal conversion unlikely. These results are consistent with our experimental observation that electron detachment out-competes hot ground state molecular fragmentation. More generally, our results reveal that the competition between molecular dissociation and electron detachment following anion photoexcitation can be determined by the magnitude of the energy gap between the excitation energy and the MECPs, rather than being a simple function of whether the excitation energy lies above the anion's vertical detachment energy.